2022
DOI: 10.3390/ijms232415723
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Troponin in Cardiomyopathy Development Caused by Mutations in Tropomyosin

Abstract: Tropomyosin (Tpm) mutations cause inherited cardiac diseases such as hypertrophic and dilated cardiomyopathies. We applied various approaches to investigate the role of cardiac troponin (Tn) and especially the troponin T (TnT) in the pathogenic effects of Tpm cardiomyopathy-associated mutations M8R, K15N, A277V, M281T, and I284V located in the overlap junction of neighboring Tpm dimers. Using co-sedimentation assay and viscosity measurements, we showed that TnT1 (fragment of TnT) stabilizes the overlap junctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…TnT1 suppressed the sliding velocity of F-actin-Tpm filaments containing ααTpm and κκTpm but did not affect the velocity of the filaments with ακTpm (Figure 10c,d). The formation of the overlap junction between the N-and C-ends of the Tpm molecule was shown to be important for the interaction of TnT1 with tropomyosin [23][24][25][26] and the Tpm regulatory function [14,21,22,[27][28][29]. The ability of the N-and C-ends of ααTpm and κκTpm to interact was determined by measuring the viscosity of the solution.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…TnT1 suppressed the sliding velocity of F-actin-Tpm filaments containing ααTpm and κκTpm but did not affect the velocity of the filaments with ακTpm (Figure 10c,d). The formation of the overlap junction between the N-and C-ends of the Tpm molecule was shown to be important for the interaction of TnT1 with tropomyosin [23][24][25][26] and the Tpm regulatory function [14,21,22,[27][28][29]. The ability of the N-and C-ends of ααTpm and κκTpm to interact was determined by measuring the viscosity of the solution.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that Tn can interact differently with ααTpm, κκTpm, and ακTpm. We previously found that the troponin T1 fragment (TnT1; residues 1-158 for rabbit fast skeletal troponin T, P02641) containing 1 site interaction with Tpm [19] enhances the affinity of ααTpm to F-actin [22]. TnT1 decreased the Tpm concentration at which half of the actin was saturated, K 50% , from 3 ± 0.2 µM to 1.25 ± 0.11 µM [22].…”
Section: Effect Of Tn On the Interaction Of ααTpm κκTpm And ακTpm Wit...mentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic testing panels have shown vast heterogeneity and diverse molecular pathways, with more than 2,000 identified sarcomere mutations. Some of the mutations are pathogenic, but most of them are benign ( 3 , 12 ). Furthermore, more evidence regarding the genotype–phenotype correlations is needed to enable the development of genetic tests or other laboratory tests for diagnosis and prediction.…”
Section: Discussionmentioning
confidence: 99%